Reformulasi Riset Penciptaan Keaktoran Teater yang Kreatif, Ilmiah, dan Terukur Berdasarkan Teks Drama - Purwanto, Purwanto (Institut Seni Indonesia Yogyakarta, 2023)
The creation of research-based role art requires proper scientific and theoretical methods. Many actors' creation results have not used logical and measurable methods, theories and processes. The process of creation based on the work of drama requires the analysis of drama as the basis of creation. Subjective considerations need to be objectified. On the other hand, the originality demands of casting work are required by examining and analyzing similarities and differences with previous similar works. The theory used is also complex, ranging from the analysis of structure and texture, actors as part of the theatre, the design of the casting work, the process of creation to the aesthetics of acting. Literature studies and practical experience can provide one solution for preparing the background of creation, the use of theatrical production theory, the position of actors in a theatre to design and methods that strengthen the creation process to become a high-quality acting work. Keywords: creativity, drama, actor, research, theatre Abstrak: Penciptaan seni peran berbasis riset membutuhkan metode ilmiah dan teori yang tepat. Sejumlah hasil penciptaan aktor belum memakai metode, teori, dan proses yang dilakukan secara logis dan terukur. Proses penciptaan berdasarkan karya drama memerlukan analisis drama sebagai dasar penciptaan. Pertimbangan yang subjektif perlu diobjektifkan. Di sisi lain, tuntutan originalitas suatu karya pemeranan dipersyaratkan dengan mencermati dan menganalisis persamaan maupun perbedaan dengan karya serupa sebelumnya. Teori yang dipakai juga kompleks, mulai dari analisis struktur dan tekstur, aktor sebagai bagian teater, rancangan karya pemeranan, proses penciptaan hingga estetika aktingnya. Kajian pustaka, dan pengalaman empirik dapat memberikan salah satu solusi untuk penyusunan latar belakang penciptaan, penggunaan teori produksi teater, posisi aktor dalam teater hingga rancangan, dan metode yang memperkuat proses penciptaan sehingga menjadi karya akting yang berkualitas tinggi..Kata kunci: kreativitas, drama, aktor, riset, teater